Semantic Paraphrase Generation Using Transformer Architectures: A Comparative Study of Pre-trained and Fine-Tuned Models - Birwadkar, RAHUL (Journal of Computer and Forensic Sciences, 2026)
Semantic paraphrase generation plays a crucial role in academic and technical writing by enabling authors to restate content while preserving its original meaning. Traditional paraphrasing approaches, such as rule-based rewriting and statistical methods, often struggle to maintain semantic consistency and linguistic fluency, especially for complex or longer text segments. Recent advances in transformer-based architectures have significantly improved text generation capabilities by leveraging contextual representations and self-attention mechanisms. This paper presents a comparative study of pre-trained and fine-tuned transformer models for semantic paraphrase generation. We evaluate encoder–decoder–based transformer architectures, with a primary focus on the BART model in both pre-trained and fine-tuned settings, alongside a large generative language model used for paraphrase generation. The fine-tuning process adapts pre-trained models to paraphrasing tasks using task-specific data, enabling improved control over semantic preservation and output consistency. The evaluation is conducted using both quantitative and qualitative analysis, including training and validation loss trends and comparative examination of generated paraphrases. Experimental results demonstrate that fine tuned transformer models produce paraphrases with higher semantic fidelity and structural coherence compared to their pre-trained counterparts, while large generative models offer fluent but less deterministic outputs. The findings highlight the importance of task-specific fine-tuning for controlled and semantically accurate paraphrase generation. This study contributes practical insights into the selection and adaptation of transformer architectures for paraphrasing applications, particularly in academic and research-oriented writing contexts.